Understanding Experiences of Fibromyalgia Patients Involved in the Fimouv Study During COVID-19 Lockdown - Colas, Claire; Jumel, Audrey; Vericel, Marie-Pierre; Barth, Nathalie; Manzanares, Jessica; Goutte, Julie; Fontana, Luc; Féasson, Léonard; Hupin, David; Guyot, Jessica (Frontiers in Psychology, 2021)
Introduction: The COVID-19 pandemic implied a period of lockdown for the general population, increasing the risk to develop some physical or mental disorders. In fibromyalgia patients, these disorders are part of the large clinical picture of the syndrome. Fibromyalgia management is especially based on a regular practice of physical activity. Lockdown imposed a break in rhythms, requiring a restructuring of scheduling. Thus, the present study aimed to investigate the experiences of fibromyalgia patients during lockdown in order to understand their experiences in adapting physical activity given the changes in everyday life using a qualitative analysis. Method: 19 patients (52 ± 9 years old) who completed a 3-month therapeutic education and/or supervised physical activity program were invited to participate (Fimouv study, Trial registration: ClinicalTrials.gov NCT04107948). A sociologist collected data by means of semi-structured interviews and analyzed them using thematic content analysis. Results: Lockdown exacerbated the main symptoms of fibromyalgia, but adjusting the rhythms of life to fluctuations of these symptoms allowed a better quality of life. Patients felt the lack of physical activity and 68% found alternatives to remain physically active. The reduction of social constraints allowed them to better contend with their pathology. Fibromyalgia stopped being a main priority. Conclusion: Lockdown was positively experienced by fibromyalgia patients. They linked the absence of physical activity with increased pain and fatigue. Nevertheless, reducing social constraints could be a key for fibromyalgia management, where symptoms seemed to take less space in everyday life.